Comparison of Isolation Frequency of Mycobacterium avium subspecies Paratuberculosis from Different Types of Samples - Mohammad Seyyedin1*, Taghi Zahraei2 and Mohsen Fathi Najafi1 (Pakistan Veterinary Journal, 2010)
Samples of faces, manure and milk of 137 dairy cattle herds were collected from different parts of Razavi Khorasan province of Iran. These herds were suspected of having Johne's disease. There were 505 faecal and manure samples and 148 raw milk samples prepared from cows affected by the clinical form of Johne's disease (n = 12), bulk milk-transporters (n = 67) and farm bulk milk tanks (n = 69). The samples were cultured on Herrold’s egg yolk medium with and without mycobactin J. The samples in which the bacteria could merely grow on Herrold’s media containing mycobactin J were considered to be positive. Diagnostic test of M. paratuberculosis culture was positive in 29 out of 137 herds. Out of faces, manure and milk samples, 50 cases were found positive. The number of bacterial colonies varied from 1 to 250. The frequency of positive and negative fecal samples taken from cows with clinical signs (n=16) and without clinical signs of Johne’s disease (n=363), 13(81.3%) and 15(4.1%) were positive, respectively. The difference in positive samples between two groups of manure samples taken from outdoors and indoors of farms was non significant. The difference in positive cases among three different types of milk samples was significant, but these differences between two groups of bulk milk-transporters and farm bulk milk tanks were non significant. Using Fisher exact test, the comparison between fecal and raw milk samples from cows with clinical signs showed non significant difference between two groups, but these differences based on the number of positive tubes and their colonies were significant.